1999
DOI: 10.1073/pnas.96.7.3447
|View full text |Cite
|
Sign up to set email alerts
|

Manganese oxide minerals: Crystal structures and economic and environmental significance

Abstract: Manganese oxide minerals have been used for thousands of years-by the ancients for pigments and to clarify glass, and today as ores of Mn metal, catalysts, and battery material. More than 30 Mn oxide minerals occur in a wide variety of geological settings. They are major components of Mn nodules that pave huge areas of the ocean f loor and bottoms of many fresh-water lakes. Mn oxide minerals are ubiquitous in soils and sediments and participate in a variety of chemical reactions that affect groundwater and bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
1,223
1
18

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,550 publications
(1,268 citation statements)
references
References 72 publications
26
1,223
1
18
Order By: Relevance
“…Oxides, carbonates and silicates are the most important Mncontaining minerals (Post, 1999). Depending on its oxidation state, Mn is utilized in countless industrial processes, such as the production of dry cell batteries, steel (Post, 1999; Saric, 1986), fuel oil additives and antiknock agents (Pfeifer et al, 2004;Ressler et al, 1999;Rollin et al, 2005).…”
Section: Manganesementioning
confidence: 99%
“…Oxides, carbonates and silicates are the most important Mncontaining minerals (Post, 1999). Depending on its oxidation state, Mn is utilized in countless industrial processes, such as the production of dry cell batteries, steel (Post, 1999; Saric, 1986), fuel oil additives and antiknock agents (Pfeifer et al, 2004;Ressler et al, 1999;Rollin et al, 2005).…”
Section: Manganesementioning
confidence: 99%
“…Natural marine and soil Mn oxides frequently have been reported to be poorly crystalline and to exhibit layer structures (Post, 1999;Manceau et al, 2005;Bodei et al, 2007). It is likely that such morphologies implicate biogenic origin.…”
Section: Comparison To Laboratory Bacteriogenic Mn Oxidesmentioning
confidence: 99%
“…It can thus be concluded that this nanoparticulate layered structural motif is characteristic of (but not necessarily unique to) laboratory biogenic Mn oxides. These conclusions lead one to question if environmental biogenic Mn oxides exhibit such characteristics (intriguingly, such features are frequently reported for poorly crystalline natural Mn oxides of possible biogenic origin (Post, 1999;Manceau et al, 2005;Bodei et al, 2007)). Establishing similarity between laboratory and environmental biogenic Mn oxides, were it to occur, would represent a significant step forward because it would provide the scientific basis to model the behavior of environmental Mn oxides based on data from laboratory studies.…”
Section: Introductionmentioning
confidence: 99%
“…Demographically these residents are more likely to be white residents of the urban core, or black South Africans working in domestic settings within the urban core or within the central business district. Most critically, manganese emitted from crustal (soil) sources such as ferromanganese smelting and mining tend to be found in more coarse particulate matter (PM 10 ) and found in the environment as inorganic manganese or manganese oxides (Post, 1999) and may not be as widely as manganese found in fine particulate matter (PM 2.5 ). Manganese from tail pipe emisssions and other combustion activities is generally found in fine PM and as manganese phosphate or sulfate which which may result in greater neurotoxicity in humans than inorganic manganese or manganese oxide exposure from ferromanganese smelting (Davis et al, 1988;Dorman et al, 2006;Normandin et al, 2004).…”
Section: Manganese Exposure In the Futurementioning
confidence: 99%